Legal Protection for Apprentices: A Review of Indonesian Labor Law - Nadhif, Faza Fatkhun (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This article discusses the legal position of apprentices based on the Manpower Law as well as the obstacles and challenges faced in the implementation of legal protection. In writing this article, the author applies normative research methods, using analysis techniques on library sources such as books, journals, and sources from internet media, based on law as a norm. Labor has an important role in the development of the country, to overcome this the government has implemented various policies, one of which is the apprenticeship program. However, it is unfortunate that many apprentices do not understand their rights, this ignorance is often exploited by irresponsible companies to employ them unfairly. One of the main obstacles in the implementation of legal protection for apprentices in Indonesia is the lack of legal awareness that plagues both companies and apprentices themselves. Unclear regulations regarding legal protection for apprentices in Indonesia are one of the significant challenges in ensuring their rights are protected. Therefore, to improve legal protection for apprentices in Indonesia, a series of integrated and sustainable improvement efforts are needed.